If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -1 = -17 + -3y Reorder the terms: -1 + 5y = -17 + -3y Solving -1 + 5y = -17 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -1 + 5y + 3y = -17 + -3y + 3y Combine like terms: 5y + 3y = 8y -1 + 8y = -17 + -3y + 3y Combine like terms: -3y + 3y = 0 -1 + 8y = -17 + 0 -1 + 8y = -17 Add '1' to each side of the equation. -1 + 1 + 8y = -17 + 1 Combine like terms: -1 + 1 = 0 0 + 8y = -17 + 1 8y = -17 + 1 Combine like terms: -17 + 1 = -16 8y = -16 Divide each side by '8'. y = -2 Simplifying y = -2
| 0.13(64)-0.33(8)= | | 2x-4-8= | | (1+j)(6-2j)= | | 6x+7(9-x)=61 | | 5x=6x-28 | | (4+3j)-(5j-6)= | | X^2+100=9x^2 | | 3(p^2-16p+81)=81 | | 12x^2-5x-3= | | 5x^2-8x-4= | | x+4=2x-1 | | 3k-3=2k+6 | | 5x+2=77 | | 54y-2y^3= | | 4x^2+28x-150=0 | | 12x^2-20x+3=0 | | 2x^2+30x+52= | | 4(2+j)-3(6+2j)+7j= | | 2(4x-7)=5(-2x-9)-5 | | 2g^2-14g+20=0 | | 4(x-2)=x-20 | | 3x-7=3x+5 | | 2(3x-1)=x+13 | | (x^2-4x+6)(2x^2+8x-1)=0 | | (x^2-4x+6)(2x^2+8x-1)=1 | | 9x+10=7x+2 | | -6y=d | | -6y=da | | w-6c=9 | | 10x+y-xy=58 | | r+5=2r-1 | | (x+5)(x-1)=0 |